A Multicenter Pilot Study Examining the Role of Circulating Tumor Cells as a Blood-Based Tumor Marker in Patients with Extensive Small-Cell Lung Cancer - Huang, Chao H.; Wick, Jo A.; Sittampalam, Gurusingham Sitta; Nirmalanandhan, Victor Sanjit; Ganti, Apar Kishor; Neupane, Prakash C.; Williamson, Stephen K.; Godwin, Andrew K.; Schmitt, Sarah; Smart, Nora J.; Spencer, Sarah; Van Veldhuizen, Peter J. (Frontiers in Oncology, 2014)
Abstract Background: SCLC, a variant of lung cancer marked by early metastases, accounts for 13% of all lung cancers diagnosed in US. Despite high response rates to treatment, it is an aggressive disease with a median survival of 9-11 months for patients with EX-SCLC. Detection of CTCs is a novel laboratory technique currently in use to determine response to therapy and to predict prognosis in breast, colorectal and prostate cancer. We initiated a study to study the role of CTC as a biomarker of response and relapse in patients with EX-SCLC. Methods: We collected blood sample from chemotherapy naïve patients with EX-SCLC prior to initiation of therapy, after completion of systemic therapy, and follow up every 6-8 weeks and at relapse. The CTC was determined using the Cell Search system in a central laboratory. The study was conducted in 4 different sites and it was reviewed and approved by respective Research Review Committee and IRBs. Results: We enrolled 27 patients with EX-SCLC, 1 was excluded due ineligibility, all patients were treated with platinum and etoposide. We observed partial response in 16 patients, stable disease in 3 patients, 1 with progression of disease and not assessed in 7 patients (5 deceased, 2 not available). The overall median number of CTCs in 24 patients measured at baseline and post-tx was 75 (range 0 to 3430) and 2 (range 0 to 526), respectively. A significant reduction in CTCs from baseline to post-treatment was identified—for the 15 subjects, the median reduction was 97.4% (range -100% to +100%, p < 0.001). Higher baseline CTC and percentage change in post treatment CTC were associated with decreased survival. Conclusions: We were able to demonstrate feasibility of using CTCs as a biomarker of response and prognosis in patients with EX-SCLC in clinical setting. CTC could be a useful biomarker in the management of EX-SCLC to predict response to therapy and predict outcome.